The gathering of reason - Sallis, John, 1938- (SUNY series in contemporary continental philosophy., 2005)
"This second edition of The Gathering of Reason expands on John Sallis's classic study of Kant's First Critique. This study examines the relation of imagination to reason and to human knowledge and action in general. Moving simultaneously at several different hermeneutical levels, Sallis carries out an interpretation of the Transcendental Dialectic of Kant's Critique of Pure Reason. Although, in contrast to the Analytic, the Dialectic seldom refers explicitly to imagination, Sallis shows that the concept of reason in the Dialectic requires the complicity of imagination. Sallis demonstrates that for Kant, reason alone does not suffice for bringing before our minds the metaphysical ideas of the soul, the world, and God; rather it is through the force of imagination that these ideas are brought forth and made effective. A new preface situates the book in relation to Sallis's later work, and an extensive afterword focuses on Kant and the Greeks."--Jacket